The phenomenon of conventional transportation in the digital era (Case study of City Transport in Medan) - Ismail Jahidin; Harmona Daulay; Ilham Saladin (Technium Social Sciences Journal, 2020)
This study aims to determine the phenomenon of city transport passengers still using city transportation (Angkot) as a preference for supporting social mobility activities. The method in this research is in the form of a case study with a qualitative approach, in which to see a picture of the phenomenon of conventional transportation in the digital era in terms of passenger rationality. The location of this research is Medan City and as a source of information related to the strategy for a real research picture, namely city transportation passengers. The type of population in this study, namely passengers from city transportation who were taken randomly, with the number of informants 35 passengers, the sampling was done purposively, and the key informants were the parties from the city transportation manager, in this case, PT Rahayu Medan Ceria (RCM) and the head of the office. Medan City Transportation Agency. Technique and data analysis by triangulation. Then also analyzed what words motivate the respondents to behave (think, feel, and act), reduce, triangulate, conclude, and verify (consult the respondent and peers again). The results and discussion in this study explain that conventional transportation is a serious problem in the future that must be solved. Policies can run effectively and efficiently and can solve the problems of conventional transportation for users. Social phenomena need attention, namely the adjustment of government policies, namely providers of good transportation service needs (cheap, safe, fast, smooth, orderly and orderly, comfortable and efficient) to be the answer to divert private vehicle users to transportation users. The decline in users of city transportation (angkot) as conventional transportation is caused by the presence of online transportation in Medan City, service facilities that are not well accepted by angkot passengers so they are reluctant to use public transportation and switch to choosing online transportation and government policies make it easier to own private vehicles with a credit system bank. In general, from the results of this study, it can be concluded that angkot passengers prefer public transportation as mobility support because the tariff is relatively cheap and is associated with convenience and other factors.